Experimental hypertrophy of myenteric neurones in the pig: A morphometric study - Brehmer, Axel; Göbel, Dieter; Frieser, Markus; Graf, Michael; Radespiel-Tröger, Martin; et al. (Neurogastroenterology and Motility, 2000)
Muscular hypertrophy in the ileum of two pigs aged 6 weeks was induced using two different surgical techniques, narrowing of the gut circumference (mechanical stenosis) and segmental reversal of an ileal loop which results in a persistent antiperistalsis of that segment (functional stenosis). These pigs were sacrificed 5-6 weeks postoperatively. Cross sections through the gut wall at various distances from the operation sites revealed marked muscular hypertrophy in the pre-stenotic regions and in the reversed segment. Whole mounts from pre- and post- stenotic, as well as reversed ileal regions, were silver-impregnated. The corresponding ileal region of a third, nonoperated pig served as control. Using a computer-aided morphometric device, somal areas of five morphological neurone types were measured at various distances orally and anally from the operation sites and along the control ileum. Values between hypertrophic and nonhypertrophic zones as well as between two corresponding zones of nonoperated ileum were compared statistically. Along the control ileum, values revealed no differences in soma sizes. Within the experimentally altered material, somal areas of type VI neurones showed marked hypertrophy related to the sites of muscular hypertrophy whereas the other types remained constant throughout (II, IV in segmental reversal) or showed slightly larger somal areas within the post-stenotic, nonhypertrophied zones (I, V, IV in stenosis). Additionally, within the reversed segment, neuronal perikarya of type I, II, IV and V neurones were larger as compared to the neighbouring regions. However, this enlargement of perikarya within the reversed segment may not be correlated with muscular hypertrophy but rather with the transections of intramural axons before reversing this segment. The results suggest that morphologically distinct neurone types may play different roles within the mechanically stressed small intestine and possibly also in the coordination of normal muscular function.